Islamic Banking Judicial Review In Accordance With Sharia Principles - Muhammad Fahrudin; Denny Kusuma; Anis Mashdurohatun (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
Islamic financial institutions, in particular of Islamic bank, is a bank that has Islamic principles in running their business which is always accompanied with the rules of Islam, both the Qur'an and Al-Sunnah. The presence of Islamic banks was greeted positively by the state to pass a law number 21 of 2008 concerning Islamic banking. But sometimes in practice the efforts of Islamic banks does not correspond with what is expected, such as the occurrence of new disputes in which the case can not be resolved by referring to the Quran and Al-Sunnah, then it is the law here which will be instrumental to run this authority as to bridge when the cases are a little tricky. In this study, the authors take issues related to Islamic banks, about how principles of Islamic banks to appropriate Shari'a and law, and as to whether the settlement of disputes in Islamic banks, this is because there are many people who are unfamiliar related to understanding the principles of Islamic banks, so expect the fore capable a reference and material considerations in understanding Islamic banking. Keywords: Judicial Review; Islamic Banking; Dispute Resolution.